City-level environmental pro-activeness in China and the European Union: differences and convergences. (22nd April 2010) - Francesch-Huidobro, Maria; Li, Vic Yu-wai; Lang, Graeme
In an attempt to meet growing environmental challenges resulting from 30 years of rapid industrialisation, China is devising new incentives to motivate cities to meet higher environmental standards aiming at a more sustainable path of development. In this article, we seek to throw light on these developments by analysing two environmental certification programmes targeted at cities established by the State Environmental Protection Agency (SEPA): the Quantitative Examination System on Comprehensive Control of Urban Environment (QESCCUE) and the National Model Cities of Environmental Protection (NMCEP). By employing a qualitative comparison with similar programmes and policy instruments used in the European Union, we seek to elucidate some of the similarities and differences in approaches to environmental governance and use of various policy instruments within these two quite different political environments.